Aminoácidos protegidos em ração para borregas mestiças - Araújo, Carolina Moreira (2018)
The use of amino acids protected from ruminal degradation is to meet the demand for metabolizable protein of ruminants. The objective of this study was to evaluate the inclusion of protected lysine and methionine in the diet of lambs. Five Dorper/Santa Inês crossbred lambs, averaging eight months of age and 50kg, were used in metabolic cages and distributed in a 5x5 latin square. The treatments consisted in the inclusion of lysine and methinine protected in doses of 0g, 8g, 16g, 24g and 32g. A digestibility test was carried out to obtain the dry matter and nutrient intakes and their digestibility. The consumption, excretion and nitrogen balance were evaluated. Protein, energy metabolites, liver and mineral enzymes and ingestion behavior were analyzed. Consumption of dry matter, crude protein, total digestible nitrients and neutral detergent fiber increased with the inclusion of amino acids. Nitrogen consumption was high in all treatments, increasing their urinary excretion. Ingestive behavior was not affected. Serum concentrations of total proteins, urea, fructosamine and gamma glutamyltransferase were high for the species, while cholesterol and lipoproteins were reduced. The inclusion of lysine and methinine up to 32 g increased MS intake and nutrients, as well as N excretion, causing possible energy losses. The metabolism was altered without causing damage to the health of the animals.